Model of Consecutive, Steady-State Underflow for Vertical Tailing Silos - Wei-cheng Ren; Ru-gao Gao; De-qing Gan; You-zhi Zhang (Advances in Materials Science and Engineering)
A continuous tailing discharge model is proposed for solving the problems of high fluctuation in underflow concentration and low, unstable actual discharge concentration in vertical tailing silos. On the basis of the mass balance equation, a mathematical model for continuous tailing discharge is derived, and a partial differential equation related to the height of the tailing silo in the compression area and tailing slurry concentration is obtained. The effective solid stress equation and the solid flux equation can be obtained from the results of centrifuge tests and intermittent sedimentation tests. The volume concentrations of underflow corresponding to various heights of tailing surfaces are simulated by using fluid mechanics software under dynamic balancing conditions. The results of the simulations are highly similar to those calculated by the derived mathematical model of continuous tailing discharge, and the results of the industrial test are also closely related to the results of the differential equation, thereby verifying the accuracy of the proposed discharge model.